Strategies for achieving graduate scholarships to the student community with Mata Garuda - Ria Wierma Putri; Triono, Agus; Sumarja, F.X; Kasmawati; Havez, Muhammad; Riyantika, Annisa (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Backgrounds: Graduate scholarships are an important resource for pursuing postgraduate studies. However, the process of obtaining scholarships often poses challenges and confusion for students. Methods: In this context, this study aims to explain the effectiveness of socialization and interactive discussions as a strategy to obtain graduate scholarships. Through socialization activities, students can obtain relevant information about the requirements, application process, and success tips in obtaining graduate scholarships. In addition, interactive discussions with fellow students who have similar experiences enable the exchange of knowledge, experiences, and strategies that are useful in facing challenges in the scholarship process. Involvement in student communities such as Mata Garuda also provides access to a wide network and emotional support which is important in motivating and guiding students during the scholarship application process. Results: Involvement in these community activities also helps students build confidence and social skills that can increase their competitiveness in obtaining graduate scholarships. Through this service, it provides important insights for students who are interested in obtaining postgraduate scholarships, especially in terms of the importance of joining student communities and taking advantage of opportunities for socialization and interactive discussions. Findings: The implication of this research is that universities and educational institutions should encourage and support student community activities that can assist students in effectively obtaining graduate scholarships.